Maintenance of postharvest storability and overall quality of ‘Jinshayou’ pummelo fruit by salicylic acid treatment - Huang, Qiang; Huang, Lulu; Chen, Jinyin; Zhang, Yajie; Kai, Wenbin; Chen, Chuying (Frontiers in Plant Science, 2023)
The loss of postharvest storability of pummelo fruit reduces its commodity value for long run. To maintain its storability, the effects of postharvest dipping treatment by salicylic acid with different concentrations (0, 0.1, 0.2, or 0.3%) were investigated on pummelo fruit (Citrus maxima Merr. cv. Jinshayou) during the room temperature storage at 20 ± 2 °C for 90 d. Among all groups, pre-storage SA treatment at 0.3% demonstrated the most outstanding ability to reduce fruit decay rate, decrease weight loss, delay peel color-turned process, and inhibit the declines in total soluble solids (TSS) as well as titratable acid (TA) content. The increases in electrolyte leakage, hydrogen peroxide (H2O2), and malondialdehyde (MDA) content of the 0.3% SA-treated pummelo fruit were reduced compared to the control (dipped in distilled water). Pummelo fruit treated with 0.3% SA exhibited the most outstanding ability to excess reactive active oxygen (ROS) accumulation, as evidenced by promoted the increases in glutathione (GSH), TP and TF contents, delayed the AsA decline, and enhanced the activities of SOD, CAT, APX, GR and POD and their encoding genes expression. Therefore, pre-storage treatment dipped with SA, particularly at 0.3%, can be used as a convenient and safe preservation method in maintaining higher postharvest storability and showing better overall quality, and thus postponing postharvest senescence and extend storage life of ‘Jinshayou’ pummelo fruit under the storage up to 90 d at room temperature.